Association of Insurance Status With Treatment and Outcomes in Pediatric Patients With Severe Traumatic Brain Injury. Issue 7 (July 2020) - Porter, Austin; Brown, Clare C.; Tilford, J. Mick; Thomas, Kevin; Maxson, R. Todd; Sexton, Kevin; Karim, Saleema; Zohoori, Namvar; Rodriguez, Analiz
Abstract : Objective: To determine whether a health insurance disparity exists among pediatric patients with severe traumatic brain injury using the National Trauma Data Bank. Design: Retrospective cohort study. Setting: National Trauma Data Bank, a dataset containing more than 800 trauma centers in the United States. Patients: Pediatric patients (< 18 yr old) with a severe isolated traumatic brain injury were identified in the National Trauma Database (years 2007–2016). Isolated traumatic brain injury was defined as patients with a head Abbreviated Injury Scale score of 3+ and excluded those with another regional Abbreviated Injury Scale of 3+. Interventions: None. Measurement and Main Results: Procedure codes were used to identify four primary treatment approaches combined into two classifications: craniotomy/craniectomy and external ventricular draining/intracranial pressure monitoring. Diagnostic criteria and procedure codes were used to identify condition at admission, including hypotension, Glasgow Coma Scale, mechanism and intent of injury, and Injury Severity Score. Children were propensity score matched using condition at admission and other characteristics to estimate multivariable logistic regression models to assess the associations among insurance status, treatment, and outcomes. Among the 12, 449 identified patients, 91.0% ( n = 11, 326) had insurance and 9.0% ( n = 1, 123) were uninsured. Uninsured patients had worse condition at admission with higher rates of hypotension and higher Injury Severity Score, when compared with publicly and privately insured patients. After propensity score matching, having insurance was associated with a 32% ( p = 0.001) and 54% ( p < 0.001) increase in the odds of cranial procedures and monitor placement, respectively. Insurance coverage was associated with 25% lower odds of inpatient mortality ( p < 0.001). Conclusions: Compared with insured pediatric patients with a traumatic brain injury, uninsured patients were in worse condition at admission and received fewer interventional procedures with a greater odds of inpatient mortality. Equalizing outcomes for uninsured children following traumatic brain injury requires a greater understanding of the factors that lead to worse condition at admission and policies to address treatment disparities if causality can be identified. Abstract : Supplemental Digital Content is available in the text.